Curriculum –Integration of Algorithmic Thinking Skills into Preschool Education - Evin Gencel, İlke (2021)
ALGOLITTLE is an EU funded Erasmus+ KA203 project seeking the ways of integrating algorithmic thinking skills into preschool education to cultivate future’s code literates starting from the earliest years. When we consider the COVID-19 outbreak process, while a transformation has been being experienced in every field, education has also been digitalized in a tremendous way. These developments promise the systems digitalized in a more global scale. Therefore, it becomes important to raise individuals with the skills allowing them to keep up with the expectations of the 21st century business world. ALGOLITTLE project consortium consists of 6 partners: İzmir Democracy University (Turkey), Scuola di Robotica (Italy), University of Maribor (Slovenia), University of Rijeka (Croatia), Instituto Politecnico de Viseu (Portugal) and Educloud Ed-Tech (Turkey). The consortium has been developing a curriculum and teaching materials to equip early childhood education undergraduates with the new skills which modern world demands and support them to become competent to meet the requirements of their future professions. Algorithmic thinking skills are defined as thinking about the steps to achieve a determined objective in a clear and detailed way (Brown, 2015). This term was suggested for the first time by Wing (2006) and is based on the studies of Seymour Papert (Papert, 1980, 1991). Wing (2006) claims that algorithmic thinking requires “solving problems, designing systems and understanding human behaviour by benefiting from the basic concepts of computer science”. And this becomes an opportunity in teacher education to ensure undergraduate students gain contemporary and innovative skills.